Efficacy of synchronized diabetes monitoring system in patients with type 2 diabetes: Preliminary results of a pilot, randomized clinical trial - Kahraman, Mustafa; Mutlu, Ummu; Ozbek, Hasan Ediz; Boz, Elif Beyza; Cakmak, Ramazan; Kurt, Serkan; Dudukcu, Hatice Vildan; Yildiz, Huseyin; Erturk, Mehmet Ali; Ozogur, Gokhan; Ozogur, Hatice Nizam; Aydin, Muhammed Ali; et al. (ELSEVIER SCI LTD, 2026)
Aim: The purpose of this study is to evaluate the applicability and efficacy of the Synchronized Diabetes Monitoring System (SDMs), which consists of a smart cap attached to insulin pens with recording, alarm, alert, and reminder functions, and software that operates via Bluetooth, in patients with type 2 diabetes on insulin treatment. Methods: The system consists of a smart mobile apparatus mounted on an insulin pen and automatically recording the dose and time of the administered insulin, an application developed for mobile phones that can read blood glucose results from the glucometer, and a website. Results: The system has been tested in a 6-month pilot cohort of SDMs group (n = 23, 44 % female, age: 50.1 f 13 years, duration: 12.2 f 9.2 years) in a transparent, controlled, and single-center pilot trial, showing promising results. The results were compared to the control group (n = 23, age: 54 f 9.3 years, 52 % female, duration: 13.8 f 7.4 years). In the third month, we found that they had better glycemic control, as indicated by a decrease in fasting blood glucose (from 147 to 114 mg/dL, p = 0.024) and HbA1c levels (from 8.5 % to 7.2 %, p = 0.003). Additionally, improvements were achieved in physical function, role limitation, and physical and mental health domains of SF-36 survey in patients using the system.
Keywords: Type 2 diabetes mellitus; Smart insulin pen cap; Blood glucose control; Remote diabetes monitoring system; Health technology; Insulin treatment; GLYCEMIC CONTROL; BASAL INSULIN; MANAGEMENT; CARE; INTERVENTION; MELLITUS; TELECARE; Endocrinology & Metabolism; General & Internal Medicine